Agent-based multipatch compartmental model for simulation of vector-borne diseases using Netlogo - Morado, Sebastian H.
Vector-borne diseases such as Dengue and Malaria depend on many factors including climate, season, geography, and human dynamics. One popular way of modeling these diseases is through compartmental models. Most compartmental models only capture temporal aspects of phenomena. With mobility patterns being a potentially significant factor in both host and vector populations for Dengue transmission, it is important to consider spatial components in these models. This work presents an agent-based multipatch (composed of several discrete regions) compartmental model to visually simulate the spread of vector-borne diseases through Netlogo. Different parameters found in the agent-based model such as transmission rate, host movement pattern, migration probability, and world shape were varied in order to study their effects on clear time (time it takes for the disease to completely die out) and the pandemic time (time it takes for the disease to spread to all regions). The results showed that host movement patterns significantly affected the average timesteps it took for the disease to reach clear time and pandemic time. Patterns which involved hosts migrating to other regions made it easier for the disease to spread throughout all regions. Other parameters such as migration probability and world shape had minor yet similar results, with one notable results being their effect on the frequency of a simulation timing out (simulation does not reach clear time or pandemic time).